Designers' guide to EN 1993-1-1 Eurocode 3, design of steel structures. - Gardner, L. (Designers' guides to the Eurocodes., 2005)
Covers many forms of steel construction and provides a comprehensive set of design guidance. This book concentrates on the commonly encountered aspects of structural steel design with an emphasis on the situation in buildings. It is useful for civil and structural engineers, code-drafting committees, and structural-design students.